UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA PAPAN BERAT SISWA KELAS 4 SD - Muhammad Anwar Romdhoni; Bambang Suteng Sulasmono; Eunice Widyanti Setyaningtyas (STKIP Persada Khatulistiwa Sintang, 2019)
Abstrack: This research is motivated by the learning outcomes of students who are still low in Ujung-Ujung SDN 03 on Mathematics. The aim of the study was to improve student learning outcomes on Mathematics subjects through the application of Teams Games Tournament assisted by heavy board media. This type of research uses Classroom Action Research (CAR). Data collection techniques are observation and test results. The research subjects were the fourth grade students of Ujung-Ujung SDN 03 totaling 18 students. Data collection tools using observation sheets, test questions are then analyzed with quantitative descriptive data. The results showed an increase in the percentage of learning outcomes of students who reached KKM in the pre-cycle, showing that from 18 there were 4 with values reaching KKM (37%) increasing in the first cycle to 14 students completing with a percentage of 78% and increasing again in cycle II reaching 100%. This increase occurs because students begin to understand the concept of Mathematics. And teachers use heavy board media that can help students understand the concept of Mathematics through the steps of learning Teams Games Tournament. Students are more enthusiastic and actively participate in each learning process.Keywords: Learning Outcomes, Mathematics, Teams Games Tournament, Heavy Board Media